Something to Have at Heart: Another Look at Memorization - Gina Briefs-Elgin (Journal of the Assembly for Expanded Perspectives on Learning, 2002)
After tracing the history of learning by heart, this essay explores its advantages and suggest that we restore this time-honored practice which can enrich our students' relationships with words and books and empower their personal lives.